2018
DOI: 10.1007/s00436-018-5797-7
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of Mabuya arajara Rebouças-Spieker, 1981 (Lacertilia: Mabuyidae) from Chapada do Araripe, northeastern Brazil

Abstract: We provide data on the helminth fauna from the digestive tract of the lizard Mabuya arajara Rebouças-Spieker, 1981 from Chapada do Araripe, northeastern Brazil. Seventy one of the 127 lizards examined (56%) were infected with four nematode species: Physalopteroides venancioi and Physaloptera sp. (Physalopteridae), Strongyluris oscari (Heterakidae), and Parapharyngodon alvarengai (Pharyngodonidae), the latter being the component species (prevalence 53.5%; mean intensity of infection 3.37 ± 2.0; discrepancy inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 72 publications
0
18
0
1
Order By: Relevance
“…There were no significant differences in the average abundance of parasites regarding host sex. Previous studies also reported no occurrence of intersexual variation related to the abundance of parasites (Amo et al, 2005; Sowemimo & Oluwafemi, 2017; Cabral et al, 2018; Ribeiro et al, 2018). This may be related to the…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…There were no significant differences in the average abundance of parasites regarding host sex. Previous studies also reported no occurrence of intersexual variation related to the abundance of parasites (Amo et al, 2005; Sowemimo & Oluwafemi, 2017; Cabral et al, 2018; Ribeiro et al, 2018). This may be related to the…”
Section: Discussionmentioning
confidence: 85%
“…Species of the phylum Nematoda showed high abundance and prevalence of infection in N . brasiliensis , which is a common pattern found in many studies with lizards worldwide, including members of the family Dactyloidae (Goldberg et al, 2006; Ávila & Silva, 2010; Cabrera-Guzmán & Garrido-Olvera, 2014; Araújo-Filho et al, 2016; Sowemimo & Oluwafemi, 2017; Cabral et al, 2018). The high abundance of these endoparasites in reptiles may be related to their life cycle, diet, and lifestyle that favors infections by this group (Cabrera-Guzmán & Garrido-Olvera, 2014; Sowemimo & Oluwafemi, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding nematodes, we registered two specimens of P. venancioi in the host small intestine. The Physalopteroides genus is distributed worldwide (Bursey & Goldberg, 1994;Al-Moussawi, 2016); however, only P. venancioi is registered in South America Ávila & Silva, 2010;Cabral et al, 2018). Despite the P. venancioi life-cycle remains poorly known (Bursey et al, 2005), this genus has heteroxenic life-cycle, with an intermediated invertebrate host and a vertebrate (amphibian, lizard, bird or small rodent) as a final host (Anderson, 2000;Al-Moussawi, 2016).…”
Section: Samplingmentioning
confidence: 99%